Delabeling, safety, and impact of β-lactam allergy testing: A systematic review - Jacqueline Loprete, MBBS; Robyn Richardson; Valerie Bramah, BSc, MOT; Simon Comben, BSc; Timothy Li, MBChB, MRCP; Liam Beiglari; Robert O’Neill, BMed Sci, MBBS; Callum McEwan, BAdvSci (Hons); Andrew Carr, DSc, MD, MBBS; Winnie Tong, MBBS, PhD; Dianne Campbell; Melanie Wong; et al. (Journal of Allergy and Clinical Immunology: Global, 2023)
Background: To improve β-lactam delabeling outcomes, we need to understand current practice and the evidence base regarding its outcomes, safety, and impact. Objectives: We sought to assess the existing published evidence reporting on the effectiveness of penicillin allergy testing and delabeling. Methods: We conducted a systematic review of studies reporting β-lactam delabeling practices and outcomes after testing, including β-lactam use and patient understanding of the delabeling result. Searches of the PubMed, Scopus, and Embase databases; clinical trial registries; and websites of professional organizations were conducted. Data were extracted from the included studies in duplicate, with a third extraction if discrepancies remained. Results: We included 284 publications (covering 98,316 participants); 173 were prospective studies, with no randomized controlled trials. The overall study quality was low. In all, 95.6% of individuals who underwent provocation testing were delabeled. Factors associated with successful delabeling could not be determined because of significant heterogeneity between studies. Anaphylaxis due to testing occurred in 0.3% of participants (95 of 31,667). Subjects who did not undergo skin testing (6,980 patients in 31 studies) before challenge had higher rates of provocation test positivity (8.8% vs 4.1% [P < .0001]) and anaphylaxis (15.9% vs 2.7% [P < .0001]) than those subjects who underwent skin testing (51,607 patients in 177 studies). Six studies (2.1%) followed patients after testing to assess their adherence to prescribing recommendations. In all, 136 participants (20.6%) were actively avoiding β-lactams despite delabeling. Conclusions: The available data suggest that penicillin allergy testing is safe and effective in delabeling most individuals, but the evidence base is incomplete and more work is required to assess the role of skin testing and the impact that delabeling is having on prescribing habits.